Собівартість продукції підприемства як фактор прийняття виробничо-господарських рішень - Танцюра, М.Ю.; Умерова, Д.Т. (Культура народов Причерноморья, 2013)
У статті розглянута собівартість продукції підприємства з різних точок зору. Розглянуто класифікацію витрат за різними критеріями, визначення собівартості продукції підприємства як фактор прийняття виробничо-господарських рішень. Ключові слова: собівартість продукції підприємства, виробничо-господарські рішення, фактор прийняття рішень. В статье рассмотрена себестоимость продукции предприятия с различных точек зрения. Рассмотрена классификация расходов по различным критериям, определение себестоимости продукции предприятия как фактор принятия производственно-хозяйственных решений. Ключевые слова: себестоимость продукции предприятия, производственно-хозяйственные решения, фактор принятия решений. In this article the cost of production enterprises from different points of view. Russian scientists are studying the problem of lowering the costs often from a position of kmenshenie material costs, which in Ukraine occupy a large proportion of the cost structure. The classification of expenditure on different criteria. Determining the cost of production of the enterprise as a factor of production and economic decision-making. According to anologii predprenimatelsk solutions we offer rozdiliti production - household decision into 4 groups: 1) the design of the production system, 2) the decision to functional production system, 3) the decision by restruktorizatsii production system, and 4) a decision on the production decision lekvidatsii. Keywords: cost of enterprise, production and business solutions, decision-making factor.